Clinical and epidemiological characteristics of COVID-19 patients with chemosensory disorders - Sergio César Lorenzo González; Elizabeth Proenza Ramírez; José Adrián Romero García; Yosvanis Leyva Zamora; Alexánder Fernández Zaldívar (Revista Cubana de Medicina Militar)
Introduction: Chemosensory disorders have been identified as typical symptoms of COVID-19. Objective: To characterize patients with COVID-19 and referred chemosensory disorders. Methods: 152 hospitalized patients, positive for COVID-19, with referred chemosensory disorders were included. Clinical and epidemiological variables, inflammation markers, chest X-ray and treatment used were studied. Results: The average age was 40.2 years, the female sex 59.2% and the antecedent prevailed, confirmed case contact (62.5%), with anosmia (95.7%), ageusia (93.3%), without comorbidities (53.3%) and absence of accompanying symptoms (36.8%). In patients with an indeterminate source of infection, confirmation was late (3.89 days); there were no significant differences between those who presented one or both disorders (p = 0.053), nor between those who did or did not present associated symptoms (p = 0.14). In 2% the neutrophil index was greater than 4; 3.3% had an absolute lymphocyte count lower than 1500x106/L and 68.4% did not show radiological alteration. 5.9% required antimicrobials and 5.3% immunomodulators; 1.3% were admitted to intensive care. Most (95.4%) were discharged from the clinic and 1.3% died. Conclusions: The female sex predominates, with ageusia or anosmia; those who do not have an epidemiological history are diagnosed with delay. There are no differences in seeking care, for one or both disorders, or for accompanying symptoms. They refer more in the absence of complications and serious pictures. Those who refer them spontaneously are generally healthy and oligosymptomatic people.